2020
DOI: 10.1089/mdr.2019.0388
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Copper Reduce Conjugative Transfer of Resistance Plasmids from Extended-Spectrum Beta-Lactamase-Producing Escherichia coli

Abstract: The present work addresses the effect of excess levels of ZnCl 2 and CuSO 4 in the growth medium on the conjugative transfer of plasmids carrying the antibiotic resistance gene bla CMY-2 from extended-spectrum betalactamase (ESBL)-producing Escherichia coli. Norwegian poultry are not treated prophylactically with antibiotics, but still, ESBL-producing E. coli are found in the chicken populations. Chickens receive higher amounts of Zn and Cu than their biological need, and several metals have been shown to act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 58 publications
(64 reference statements)
4
20
0
Order By: Relevance
“…The rise in multi-drug resistant bacteria has sparked concern around the world, especially in Gram-negative pathogens (Young, 2013). Our previous work showed that zinc could block the emergence of new antibiotic resistance in vitro in E. coli, Klebsiella pneumoniae, and Enterobacter cloacae (Bunnell et al, 2017;Crane et al, 2018), and this was confirmed by other investigators (Buberg et al, 2020). The inhibitory effect of zinc on SOS-induced antibiotic resistance was also observed in vivo .…”
Section: Discussionsupporting
confidence: 70%
“…The rise in multi-drug resistant bacteria has sparked concern around the world, especially in Gram-negative pathogens (Young, 2013). Our previous work showed that zinc could block the emergence of new antibiotic resistance in vitro in E. coli, Klebsiella pneumoniae, and Enterobacter cloacae (Bunnell et al, 2017;Crane et al, 2018), and this was confirmed by other investigators (Buberg et al, 2020). The inhibitory effect of zinc on SOS-induced antibiotic resistance was also observed in vivo .…”
Section: Discussionsupporting
confidence: 70%
“…A previous report showed that Cu 2+ and CuO nanoparticles at 100 µmol/L could decrease the horizontal transfer of plasmid-mediated ARGs due to the reduced recipient number (Zhang et al, 2019). Higher sub-MIC concentrations of Cu 2+ reduced conjugative transfer of plasmids (Buberg et al, 2020). As reported, 100 µmol/L Cu 2+ suppressed the transfer of plasmid-mediated ARG in a sludge bacterial community, probably attributed to disrupted iron-sulfur clusters of metalloenzymes and the purified fumarase A poisoning (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Beta-lactamases, as well as integron and plasmid-encoded extended-spectrum beta-lactamases (ESBLs), are responsible for contributing resistance against cephalosporin and penicillin. Beta-lactamase inhibitors interfere with the enzyme by plasmid but not by AmpC gene (Buberg et al 2020).…”
Section: Modification and Inactivation Of Antibioticsmentioning
confidence: 99%